Rhetoric of international development targets and the reality of official development assistance - Mehrotra, Santosh (UNICEF. Innocenti Research Centre FlorenceIT, 2001)
Examines the extent to which poverty alleviation through support for basic social services has become part of the official development assistance (ODA) strategy of donors. Outlines the institutional response of donor governments to the International Development Targets (IDTs), analyzes trends in overall ODA and in ODA targeted at basic social services. Examines the sectoral composition of aid to basic services, as well as qualitative issues and new developments in policies related to these sectors. Calls for the removal of barriers to new exports from developing to industrialized countries.